2016
DOI: 10.1177/2324709616636398
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Sepsis Complicated by Splenic Abscesses and Purpura Fulminans in a 15-Month-Old Child

Abstract: Streptococcus pneumoniae is an invasive organism that causes a wide range of common diseases, including sinusitis, acute otitis media, and pneumonia. Splenic abscesses and purpura fulminans (PF) are rare complications of pneumococcal disease. Splenic abscesses caused by S pneumoniae have only been reported in the adult literature. PF has been described in the pediatric population as a rare complication in patients with invasive pneumococcal disease (IPD) with and without underlying immunological disorders such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In addition, although relatively infrequent, pneumococcal pyelonephritis, urosepsis and urinary tract infections have been reported [ 10 , 11 ]. Metastatic pyogenic infections can occur during the course of bacteremia caused by invasive pneumococcal disease with and without underlying immunological disorders [ 12 , 13 ]. Lantinga et al [ 2 ] conducted a systematic review from 1948 to 2014 and reported that various pathogenic microorganisms, including bacteria and fungi, were causative agents according to microbiological results and pathogens isolated in renal cyst infections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although relatively infrequent, pneumococcal pyelonephritis, urosepsis and urinary tract infections have been reported [ 10 , 11 ]. Metastatic pyogenic infections can occur during the course of bacteremia caused by invasive pneumococcal disease with and without underlying immunological disorders [ 12 , 13 ]. Lantinga et al [ 2 ] conducted a systematic review from 1948 to 2014 and reported that various pathogenic microorganisms, including bacteria and fungi, were causative agents according to microbiological results and pathogens isolated in renal cyst infections.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published cases in the literature occur in those patients with some form of immunodeficiency. Only a few cases have reported this dramatic of a presentation in otherwise healthy patients [11,[35][36][37]. Asplenia is a significant risk factor, as illustrated in the case of an otherwise healthy 36-yearold mother of 2 who died 12 hours after symptom onset despite timely and appropriate therapy [38].…”
Section: Discussionmentioning
confidence: 99%